Genetic Variability of Indels in the Prolactin and Dopamine Receptor D2 Genes and Their Association with the Yield of Allanto-Amniotic Fluid in Russian White Laying Hens - Anna A. Krutıkova; Elena S. Fedorova; Michael Romanov; Olga İ. Stanıshevskaya; Mikhail G. Smaragdov; Andrei A. Kudınov; Valeriy P. Terletsky; Natalia V. Dementıeva; Olga V. Mıtrofanova; Nikolai V. Pleshanov (Journal of Agricultural Sciences)
Currently, there is virtually no information on genetic factors affecting the yield of allanto-amniotic fluid, which is the raw material for the production of human and animal vaccines. Association studies including this trait are beneficial for increasing productivity of a biotechnological line of chickens used for the production of ‘Clean Eggs’. We examined here a population of the Russian White breed for the effects of indels in the prolactin (PRL) and dopamine receptor D2 (DRD2) genes on the yield of extraembryonic fluid (YEF) and embryo weight at 12.5 days of development. A 24-bp insertion in the 5' flanking region of the PRL gene significantly (P<0.01) increases YEF in the embryos. The heterozygous embryos contained the highest YEF (9.6 mL) than that of the homozygous insertion (9.4 mL) and deletion embryos (8.4 mL). We also found a significant association (P<0.001) between the PRL genotypes and egg weight (EW). The results of the present study suggest a significant association between the PRL gene variation and quantitative traits in the Russian White chickens, contributing to a long-term programme on the effective use of the genetic potential of Russian gene pool breeds and populations of chickens.